2021
DOI: 10.21091/mppa.2021.4031
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Musculoskeletal Complaints in Female Musicians: A Systematic Review and Exploration for Future Studies

Abstract: BACKGROUND: Female musicians are prone to the development of musculoskeletal complaints (MSC). The etiology of this increased risk is poorly understood. As the number of professional female musicians increases, so does the importance of understanding female-specific risk factors for MSC in musicians. OBJECTIVE: To provide an overview of current literature of proven and possible risk factors/etiology of MSC in female musicians, and to identify topics for future studies. METHODS: Systematic review performed acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our results also showed that most students using the PAHC facilities were female (58.7%). This is in line with other studies indicating that female musicians appear to be more likely to develop injuries compared to male musicians ( Manchester and Cayea, 1998 ; Baadjou et al, 2016 ; Kok et al, 2016 ; Borger et al, 2021 ). However, another explanation for the higher percentage of female music students visiting PAHC could also be that they tend to ask for support in an earlier stage.…”
Section: Discussionsupporting
confidence: 93%
“…Our results also showed that most students using the PAHC facilities were female (58.7%). This is in line with other studies indicating that female musicians appear to be more likely to develop injuries compared to male musicians ( Manchester and Cayea, 1998 ; Baadjou et al, 2016 ; Kok et al, 2016 ; Borger et al, 2021 ). However, another explanation for the higher percentage of female music students visiting PAHC could also be that they tend to ask for support in an earlier stage.…”
Section: Discussionsupporting
confidence: 93%
“…For young student musicians, PRMD has more serious impacts and consequences. Past literature has found that inexperienced musicians are more susceptible to PRMD (Borger et al, 2021;). In addition, PRMD may cause music students to delay learning or even abandon their studies (Kok et al, 2016;Arnason et al, 2014;Ioannou et al, 2018).…”
Section: Introductionmentioning
confidence: 98%